CHANGES IN THE DIETARY PATTERNS OF PREGNANT ADOLESCENTS IN PRIMARY CARE IN ALAGOAS BETWEEN 2015 AND 2022 (REMUNOM, 2025)
This study evaluated the temporal trend of dietary consumption among adolescent pregnant women assisted by primary health care in Alagoas, Brazil, between 2015 and 2022, focusing on the degree of food processing. Secondary data from the Food and Nutritional Surveillance System (SISVAN) were analyzed, including 100 pregnant adolescents in 2015 and 126 in 2022. Most dietary markers remained stable over time, including the consumption of fruits, vegetables, beans, instant noodles, snacks, cookies, and sweetened beverages. The only significant change was observed in the consumption of hamburgers and processed meats, which increased from 35.0% to 52.4%, indicating a growing trend. These findings highlight the persistence of unhealthy dietary patterns and increased intake of high-calorie ultra-processed foods, potentially contributing to excessive weight gain and adverse maternal-fetal outcomes. The study underscores the importance of nutritional education and interventions during prenatal care to promote healthier food choices among adolescent pregnant women.